Teaching, learning and assessments (TLA) in civil engineering laboratory courses in open distance learning (ODL) during COVID-19 pandemic / Fei Ha Chiew ... [et al.] - Fei, Ha Chiew; Noh, Narita; Chai, Lian Oh; Mohd Noor, Nur Asmaliza; Mat Isa, Che Maznah (Universiti Teknologi MARA, 2022)
The Covid-19 pandemic has brought about a true challenge to students and educators in the teaching, learning and assessment (TLA) of the psychomotor domain integral in laboratory experiment and design work. The pandemic has opened venues for open distance learning (ODL) with a completely new outlook for educators. The objective of this paper is to examine the suitability of the alternative TLA methods adopted in laboratory courses in ODL during the pandemic. Document review was carried out on various laboratory courses for a civil engineering programme in Universiti Teknologi MARA. The findings show that the assessment methods commonly used during ODL are individual and group reports, lab demonstration, video presentation, laboratory projects, online tests, individual online interviews, home-based mini projects, peer evaluation, and simulation using various software. Each alternative assessment was evaluated based on three (3) criteria which are the relevancy of knowledge, TLA activities, and suitability of the TLA activities to address the respective learning domain of the courses. Overall, the alternative assessment methods used during ODL were found to be relevant in imparting knowledge in laboratory courses, except for the development of specialist knowledge (WK4) as students are not able to utilize the equipment in the laboratory. Meanwhile, alternative activities are found less suitable to address the psychomotor domain imparted in the learning outcomes that involve specified equipment or machinery. Finally, the alternative assessments are found to effectively capture the cognitive skills and the programme outcomes related to knowledge application (PO1) and analysis (PO2) but are less effective in capturing investigation skills (PO4) addressing the psychomotor domain.